Environmental management amongst manufacturing firms in Malaysia / Roaimah Omar and Rachel Samuel - Omar, Roaimah; Samuel, Rachel (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
In many Asian countries, firms are required by the government to consider sustainable development as an integral aspect of the firms’ business strategy. Besides, the growing demand for environmentally friendly products among consumers has driven many businesses to be concerned about green marketing and sustainable development. Implementation of environmental standards amongst companies is costly and difficult. This study was undertaken to examine the stages of environmental management amongst companies in Malaysia. In Malaysia, SMEs play an important role in continuous economic growth. Preliminary results indicate that the stage of environmental management is moderate whereby environmental management is perceived worthwhile and companies are driven by ethical concern or corporate social responsibility. For a small percentage, environmental management is deemed unnecessary or as an inconvenience. This exploratory study hopes to bring forth the importance of environmental management towards business sustainability.